2014
DOI: 10.1016/j.egypro.2014.11.341
|View full text |Cite
|
Sign up to set email alerts
|

Simulations of the Impact of Co-injected Gases on CO2 Storage, the SIGARRR Project: First Results on Water-gas Interactions Modeling

Abstract: When capturing CO 2 , the collected gas mixture can vary considerably both qualitatively and quantitatively, based on the CO 2 origin, the capture process and the industrial sector. Co-injected with CO 2 , these impurities might be an issue in case of leakage but may also impact the subsurface storage. Operators of the whole CCS chain are therefore waiting for recommendations in terms of admissible concentrations while regulators are waiting for tools allowing them to formulate these recommendations. The SIGAR… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 27 publications
0
12
0
Order By: Relevance
“…Similarly, numerical simulations are interesting tools when the considered molecules are toxic for human, which is typically the case of systems containing H 2 S . In numerous studies we have reported the use of molecular simulation techniques to obtain pseudo experimental data for gas mixtures . In these studies, simulated vapour‐liquid equilibrium data were compared to corresponding experimental data points, and scaling laws together with additional molecular simulation results were used to calculate critical point coordinates .…”
Section: Computational Methods and Resourcesmentioning
confidence: 99%
“…Similarly, numerical simulations are interesting tools when the considered molecules are toxic for human, which is typically the case of systems containing H 2 S . In numerous studies we have reported the use of molecular simulation techniques to obtain pseudo experimental data for gas mixtures . In these studies, simulated vapour‐liquid equilibrium data were compared to corresponding experimental data points, and scaling laws together with additional molecular simulation results were used to calculate critical point coordinates .…”
Section: Computational Methods and Resourcesmentioning
confidence: 99%
“…Søreide and Whitson (1992) adapted the Peng-Robinson EOS (Peng and Robinson 1976); Duan and Sun (2003) derived a virial EOS; and Spycher et al (2003) employed a cubic EOS (Redlich and Kwong 1949). Various geochemical solvers were recently developed with specific modules to incorporate the cubic EOS to address non-ideal gas phases at high pressures and temperatures (Appelo et al 2014;Corvisier et al 2014;Leal et al 2014). The phase equilibrium is presented below.…”
Section: Chemical Equilibrium and Mass Balancesmentioning
confidence: 99%
“…The classic cubic EOS formulation and mixing rule are general, i.e., applicable to every compound. Their ability to accurately represent the CO 2 -H 2 O and CO 2 -H 2 O-NaCl systems was demonstrated (Spycher et al 2003;Spycher and Pruess 2005;Corvisier et al 2014Corvisier et al , 2017Hajiw et al 2018), in addition to other systems that include various compounds and gaseous mixtures. A comparison between experimental data and several other methods yielded good results (Hajiw et al 2018).…”
Section: Equation Of Statementioning
confidence: 99%
See 2 more Smart Citations